Stop That Train. - Mandelbaum, R. (IEEE spectrum)
George Westinghouse's many inventions rank him with Thomas A. Edison and Werner von Siemens as founding fathers of our electrified world. Yet, ironically, Westinghouse's first invention, a railroad brake he patented in 1869, was actuated not by electrons but by air. To this day, most railroads rely on that system's principle of releasing air from a pressurized pipe that runs the length of the train and brakes the cars one after the other, at a rate of 152 meters per second. In the past decade, however, the idea of using electrical mechanisms has reemerged in a hybrid system that uses an electronic system to control a pneumatic one, so as to set the brakes in all the cars simultaneously. So obvious are the advantages of the new technology - called electronically controlled pneumatic braking, or ECP for short - that its manufacturers are optimistic it will eventually sweep the field.